WiNGBEARER - Liu, Marjorie M.; Issakhanian, Teny; HarperCollins (Firm) (New York, NY : Quill Tree Books, HarperAlley, imprints of HarperCollins Publishers, 2022)
"Zuli is extraordinary--she just doesn't realize it yet. Raised by mystical bird spirits in the branches of the Great Tree, she's never ventured beyond this safe haven. She's never had to. Until now. When a sinister force threatens the life-giving magic of the tree, Zuli, along with her guardian owl, Frowly, must get to the root of it. So begins an adventure bigger than anything Zuli could've ever imagined--one that will bring her, along with some newfound friends, face-to-face with an ancient dragon, the so-called Witch-Queen, and most surprisingly of all: her true identity. This captivating middle grade graphic novel, the first of a series, is perfect for fans of the Amulet books and the Wings of Fire series."-- Provided by publisher.
Keywords: Imaginary wars and battles -- Comic books, strips, etc; Voyages and travels -- Comic books, strips, etc; Birds -- Comic books, strips, etc; Fantasy comic books, strips, etc; Adventure story comics